Building a storybrand : clarify your message so customers will listen - Miller, Donald, 1971- (HarperCollins Leadership, an imprint of HarperCollins, 2017)
"Explains how businesses can better connect with their customers through the use of a simplified brand message, one that fosters ease of understanding on websites, in brochures, and on social media."